Soft Computing for Problem Solving SocProS 2017, Volume 1 - Bansal, Jagdish Chand; Das, Kedar Nath.; Nagar, Atulya; Deep, Kusum; Ojha, Akshay Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This two-volume book presents outcomes of the 7th International Conference on Soft Computing for Problem Solving, SocProS 2017. This conference is a joint technical collaboration between the Soft Computing Research Society, Liverpool Hope University (UK), the Indian Institute of Technology Roorkee, the South Asian University New Delhi and the National Institute of Technology Silchar, and brings together researchers, engineers and practitioners to discuss thought-provoking developments and challenges in order to select potential future directions The book presents the latest advances and innovations in the interdisciplinary areas of soft computing, including original research papers in the areas including, but not limited to, algorithms (artificial immune systems, artificial neural networks, genetic algorithms, genetic programming, and particle swarm optimization) and applications (control systems, data mining and clustering, finance, weather forecasting, game theory, business and forecasting applications). It is a valuable resource for both young and experienced researchers dealing with complex and intricate real-world problems for which finding a solution by traditional methods is a difficult task.
Hindi Speech Synthesis Using Paralinguistic Content Expression -- Stability Analysis and Controller Design for Unstable Systems Using Relay Feedback Approach -- A Novel Approach to Handling Forecasting Problems Based on Moving Average Two-factors Fuzzy Time Series -- Linking Brainstem Cholinergic Input to Thalamocortical Circuitry -- Using NSGA-II to Solve Interactive Fuzzy Multi-objective Reliability Optimization in Complex System -- Detecting Image Forgery in Single-sensor Multispectral Images -- A Hardware Architecture Based on Genetic Clustering for Colour Image Segmentation -- Bat Algorithm Based Traffic Signal Optimization Problem.
Keywords: Computational intelligence; Signal processing; Artificial intelligence; Computational Intelligence; Signal, Speech and Image Processing; Artificial Intelligence